The Relationship Of Kalam Science, Philosophy And Tasawuf (A Review Of Its Role And Function In Creating Insan Kamil) - Jannah, Fathul; Zuliana, Eka; Ridwan , Ahmad; Prame Shela, Icha (Education Achievement: Journal of Science and Research, 2022)
Knowledge of Islamic Science, Philosophy, and Sufism is often separated in the study of Islamic thought, even though in reality the three are closely related. If examined more deeply, Kalam Science and Sufism initially had an inseparable relationship, especially in the search for truth. Kalam science seeks truth through reason which still refers to the texts of the Koran and al-Hadith. The discussion in Ilmu Kalam includes the concepts of faith, kufr, hypocrisy, various sects, but it all boils down to the search for the truth of faith. Meanwhile, in Sufism, the essence of truth is discovered through direct experience and spiritual appreciation, passing through various stages of station. Meanwhile, in philosophy, truth is obtained through human intellectual power. By studying these three sciences, it is hoped that someone can reflect themselves as a complete human being, spiritually and intellectually.